Another story about Šaban Bajramović – /B/Lueser from the South Side - Todorović, Dragan M. (Sociološki pregled, 2019)
Šaban Bajramović was the most fruitful and most important, and certainly most famous and most popular Romani singer, composer and poet in the Balkans, crowned with the title “Tsar” of Romani music. He also represents an institution and authentic cultural value of a national group - the Romani, who continue the struggle for a dignified place under the heavenly vault even in the twenty-first century. The book by Dragoljub B. Djordjević, a Nišian sociologist of religion and a romologue, titled “I asked a little snail: my sociological story about Šaban Bajramović”, published by Službeni glasnik from Belgrade, testifies about what needs to be done so that he can posthumously retain what he had achieved in life.